Performance-Based evaluation : - Hale, Judith A. (Jossey-Bass, 2002)
If you are an experienced trainer, an instructional designer, a specialist in performance improvement, or a manager responsible for learning and performance, Performance-Based Evaluation . . . offers you the proven tools and information to evaluate programs and people performance. Filled with real-world examples, this practical resource will help you to determine what to do and (just as important) what not to do. Performance-Based Evaluation contains a wealth of information including: Suggestions on how to measure both hard and soft skills Guidance on measuring required and mandated programs Ideas for measuring elective training and employee relations programs Procedures for comparing different delivery systems Information on how to sample people and documents Tips for both collecting data and information on analyzing data using descriptive and inferential statistics In addition, the book includes a CD-ROM with customizable and reproducible job aids, charts, and exercises.